Decolonising restorative justice in Indonesia: a comparative study across Customary Law traditions - Agus Widjajanto; I Gde Pantja Astawa; Muhammad Rulyandi (Faculty of Law, University of Muhammadiyah Malang, 2025)
This article interrogates the Western genealogy of restorative justice by mobilising Indonesia’s living law as a co-constitutive legal ontology. It investigates how Indonesian customary justice conceptualises harm, accountability, and repair, and how its normative logics can be translated into doctrine for pluralist penal reform. Methodologically, a normative (doctrinal) design with a decolonial, epistemic justice orientation is applied to constitutional and statutory texts, sub-regulations, case law, and recorded customary norms/oral traditions. The research analysis proceeds through hermeneutic–interpretive reading, a structured comparative matrix (authority locus, procedure, remedy typology, and ritual closure), and an abductive synthesis generating mid-level propositions. The research finds that crime is framed as a relational breach rather than solely an offence against the state; authority is communally distributed; remedies integrate material, symbolic, and service components; and ritual reintegration supplies closure. Where timely notice, freely given consent, accredited facilitation, translation, and written records are present, these processes satisfy core penological aims while remaining compatible with due process baselines. Theoretically, adat is repositioned as an equal source of restorative reasons. Normatively, we propose rule level pathways: to amend Criminal Code Law No. 1/2023, Article 2 (“living law”) to add (i) a complementarity/sufficiency clause recognising adat settlements meeting due process minima for eligible offences and (ii) a subsidiarity clause routing cases to state forums only where those minima fail or public safety thresholds require it; harmonise and strengthen restorative “gateways” in regulations of the Office of the Attorney General (2020) and the National Police (2021); craft a narrowly tailored adult diversion track; and institute accreditation, registry, independent review, and piloted roll outs with transparent metrics, presenting Indonesian customary law as a generative jurisprudence for penal reform.